Precision medicine in rheumatoid arthritis: Evaluation of a new approach to predict clinical response to methotrexate in patients with early rheumatoid arthritis - Alejandro Escudero; Mercedes Alperi; Ana Isabel Turrion; Rosario Lopez; Tatiana Yebra; Gema Cordero; Teresa Diez; Isabel Portero; Francisco J. Blanco (PLoS ONE, 2025)
Background International guidelines recommend methotrexate (MTX) as the first-choice treatment in rheumatoid arthritis (RA). Although most patients with recently diagnosed arthritis achieve low disease activity or remission with MTX, about 30–40% do not significantly decrease disease activity after 6-month treatment. Predicting response is essential for choosing the best therapeutic option during the window of opportunity. Objective This study aimed to evaluate the performance of two new tests measuring the in vitro response to MTX in MTX-naive patients with RA and the association of the test results with clinical remission after 6-month treatment with MTX. Methods This prospective 6-month study was conducted on 31 RA patients starting MTX treatment. Monocyte metabolic activity (Monocytes Test) and reactive oxygen species (ROS Test) in peripheral blood were measured in vitro before treatment, and response to MTX and remission was measured at 6 months. The area under the receiver operating characteristic curve (AUC) for predicting 6-month remission was calculated with 95% confidence intervals (CI) for each test. Results Patients in remission (71%) and not in remission (29%) at 6 months showed no statistically significant clinical differences at baseline. They only differed in test results: ROS levels were higher in patients who achieved 6-month remission than in those who did not (p < 0.001), and monocyte levels were lower in patients who achieved remission than in those who did not (p < 0.05). Prediction accuracy was high, with AUC values of 0.919 (95% CI [0.813–1.025]) and 0.826 (95% CI [0.664–0.989]), respectively, for ROS and monocyte levels. Conclusions In MTX-naive patients with RA, the pharmacological response to MTX can be adequately predicted in vitro by quantifying ROS production and total monocytes from peripheral blood mononuclear cells.